Bacterial Etiology and Antibiotic Susceptibility Patterns in Urinary Tract Infection among Patients with Various Renal Conditions - Saleem, Mavra; Shahzad, Khawar Ali; Munawer, Muhammad Faizan; Marryum, Munazzah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
Urinary tract infections (UTIs) are a common medical problem affecting a significant number of individuals around the world. The administration of UTIs in patients with renal abnormalities can be challenging, as these patients might require specific consideration and antibiotic regimens. The purpose of this study, which was carried out in the District Bahawalpur, was to investigate the prevalence, bacterial composition, and antimicrobial resistance pattern of UTIs in individuals with renal conditions, including renal calculi, renal cysts, and renal failure. In this descriptive cross-sectional study, 50 clinical samples from Bahawal Victoria Hospital, Bahawalpur, were subjected to microbiologic analysis using urine culture and drug susceptibility testing, and statistical analysis using descriptive statistics. Mean Patient Age was 28.52 ± 2.99, and the female to male ratio was 27:23. Among 50 patients 44% had right kidney stones, and 56% of patients faced UTIs for the first time. The most common pathogen was Escherichia coli (E. coli) (50%), which was followed by Klebsiella spp (20%), Pseudomonas spp (16%), Morganella spp (8%), and Staphylococcus aureus (6%). Azetronam was effective against some bacteria, including 4.0% of Escherichia coli and 8.0% of Klebsiella spp. Amoxicillin and Polymyxin were less effective than Augmentin and Amikacin, which were the most often used antibiotics. Our study demonstrates that antibiotic selection based on bacterial etiology is crucial for effective UTI treatment in patients with renal abnormalities. These findings improve patient outcomes and address the challenge of antibiotic resistance in patients with renal conditions.